2021
DOI: 10.1016/j.hrtlng.2021.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Lung ultrasound score as a tool to monitor disease progression and detect ventilator-associated pneumonia during COVID-19-associated ARDS

Abstract: Background Lung ultrasound can accurately detect pandemic coronavirus disease (COVID-19) pulmonary lesions. A lung ultrasound score (LUS) was developed to improve reproducibility of the technique. Objectives To evaluate the clinical value of LUS monitoring to guide COVID-19-associated acute respiratory distress syndrome (ARDS) management. Methods We conducted a single center, prospective observational study, including all patients admitted wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 30 publications
1
27
0
Order By: Relevance
“…The number of B-lines to consider a lung area as containing interstitial syndrome which is an alteration in the lung parenchyma between air and fluid filled areas that are not normally present without pathology, has been established as 3 or more by international consensus [39]. Furthermore, several studies looking to assess the use of the lung ultrasound score (LUSS) for predicting disease severity in COVID-19 patients have used the criterion of 3 B-lines or more as well as a cut-off for the consolidation size [40,41]. Therefore, the score by Soldati et al [38] was modified to reflect evidence appearing recently in the literature that assesses disease severity both in hospitalized and intensive care unit (ICU) patients as suggested by the mentioned studies.…”
Section: Lung Ultrasound Scorementioning
confidence: 99%
See 2 more Smart Citations
“…The number of B-lines to consider a lung area as containing interstitial syndrome which is an alteration in the lung parenchyma between air and fluid filled areas that are not normally present without pathology, has been established as 3 or more by international consensus [39]. Furthermore, several studies looking to assess the use of the lung ultrasound score (LUSS) for predicting disease severity in COVID-19 patients have used the criterion of 3 B-lines or more as well as a cut-off for the consolidation size [40,41]. Therefore, the score by Soldati et al [38] was modified to reflect evidence appearing recently in the literature that assesses disease severity both in hospitalized and intensive care unit (ICU) patients as suggested by the mentioned studies.…”
Section: Lung Ultrasound Scorementioning
confidence: 99%
“…These indicators could assist hospital or government managers in the planning and allocation of scarce medical resources. Moreover, the LUSS has been used to identify the development of ventilatorassociated pneumonia in ICU patients [40] and thus had a direct impact on their medical management. Although studies assessing the LUSS in the prediction of mortality have been mixed [22,40,43], the potential to incorporate this new quantified assessment into more complex prediction models would be a promising avenue for further research.…”
Section: Lung Ultrasound Scorementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, pleural line thickening with uneven B lines is a notable pattern, suggesting that the patient may be complicated by pulmonary fibrosis, an important factor influencing pulmonary function in COVID-19 patients [ 18 ]. Additionally, recent studies proposed a more precise evaluation standard, namely LUS score (LUSS), and demonstrated that LUSS was correlated to disease severity and progression [ 19 ], and had a good agreement with COVID-19 patients outcomes [ 20 – 22 ].…”
Section: Main Textmentioning
confidence: 99%
“…Screening the patient and aiding precise triage and treatment allocation in both the emergency and ICU departments 3. Assessing the lung lesions' progress and evaluating the severity of COVID-19 [ 10 , 12 , 18 , 19 ] 4. Combing with echocardiography, diaphragmatic ultrasound and other aspects to guide the comprehensive treatments for COVID-19 related ARDS and monitor the response to treatments Echocardiography 1.…”
Section: Introductionmentioning
confidence: 99%